PENGARUH PELATIHAN TAWA TERHADAP PENURUNAN TINGKAT STRES PADA LANJUT USIA (LANSIA) YANG TINGGAL DI PANTI WERDHA HARGO DEDALI - Esterina Fitri Lestari (Jurnal Psikologi Tabularasa, 2011)
This study aims to determine is there influence between laughter training on reducing stress levels in the elderly in a nursing institution Hargo Dedali.Stressthat occursin the elderlycaused byan inabilityto adapt oradjust themselvesto the environmentas well aslowerthe changes that occurredin his life, feelingdepressedandlonely,andfeeling isolated,removed,andis not required. The research was conducted in elderly in nursing InstitutionHargo Dedali. the number of study subjects 14 people, consisting of a control group of 7 people and 7 experimental groups.Scale data collection tool in the form of stress levels in the elderly consisting of 59 items.Data analysis was performed with statistical techniques Mann-Whitney U-Test, with the help of statistical program SPSS version 12.0. From the analysis of research data obtained siginifikansi value of 0.04.This suggests that there is influence between laughter training to decrease the stress levels in the elderly in a nursing institution Hargo Dedali. Keywords: Training Laughter, Stress, Elder